Art, archaeology & science an interdisciplinary approach to Chinese archaeological and artistic materials - Yang, Meili (Brighton Sussex Academic Press, 2016)
"Science has played a crucial role in the initial stages of westerners' collecting and studying ancient Chinese artworks and archaeological materials. The relevant scientific data were quickly generated using progressively sophisticated examination techniques. But the task of integrating scientific data with archaeological and art historical resources, and developing a workable interdisciplinary study method, has lagged behind scientific endeavor. Part One of this book explores the modes and functions of the scientific resources available and their integration into interdisciplinary study methods and models; pre-war researchers particularly emphasized that their studies of Chinese artistic/archaeological materials were scientific. Improvements in precision and advanced specialization of examining instruments and techniques resulted in substantively more detailed scientific data, particularly in the post-war period. This brought with it new research dimensions and increased knowledge of targeted samples, and also greater challenges to the integration of interdisciplinary study. In Part Two, Meili Yang establishes a feasible method of interdisciplinary study in terms of five case studies related to Chinese Song ceramics. Relevant data are provided and professionally explained, resulting in critical new information related to contemporary ceramic technologies. This technology information leads us to the recognition of the uniqueness of each single artwork and the artisan's individual intention - and critically, recognition of the close association with contemporary society and culture at the time of manufacture"
Introduction -- Science, art and archaeology -- Scientific study of archaeological materials during the Chinese Song Dynasty : a Shen Kua case study -- The role of science in western Chinese jade collection and knowledge creation : a case study -- Modern western science in initial Chinese archaeology development -- Scientific study of Chinese archaeological materials in the pre-war period : Berthold Laufer's Han porcelain case study -- Qinghe and Song shards : rethinking Palmgren's scientific investigation in pre-war China -- Ceramic technology and art in Song society -- Ancient Chinese shards in the post-war West : science and art perspectives -- Technological variations and the artist's intention : a case study of Chinese southern Song Guan imperial ware -- Technology and art in society : the significance of "furnace transmutation" in Chinese Song Jun ware -- Sintering technology and art in Chinese Song Ding white ware -- Beyond cross-technology : a case study of Chinese Song imperial Ru in Jun glaze.
Includes bibliographical references and index.
Keywords: Archaeology -- Methodology; Archaeology -- Technological innovations; Archaeology and art -- Case studies; Pottery, Chinese -- Song-Yuan dynasties, 960-1368 -- Case studies; China -- Antiquities -- Case studies